Informative value of some endocrine homeostatic parameters in the formation of endometrial cancer risk groups - Yu. S. Sidorenko; E.. A Shurygina; O. G. Shishkina; V. V. Gorobtsova (Опухоли женской репродуктивной системы, 2014)
Twenty-five patients with atypical endometrial hyperplasia (AEH) and 90 patients with Stages I-II endometrial cancer (EC) were followed up. The patients’ mean age was 44.3±2.1 years. A control group consisted of 20 healthy women matched for age. Before treatment, the authors determined the blood levels of adrenocorticotropic hormone and cortisol by radiometric assay and the content of daily excreted cortisol, cortisone, tetrahydrocortisol, tetrahydrocortisone, 11-hydroxy-17-ketosteroids, estrone, estradiol, and pregnanediol by the conventional classical studies.The nature of the impaired synthesis and metabolism of sex and adrenocorticoid hormones and their degree have been found to coincide, which suggest that it is expedient to use these findings to form EC risk groups in patients with AEH in the late reproductive period.